EFEKTIVITAS PENGGUNAAN BAHAN AJAR BERBASIS RME UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA FASE B SEKOLAH DASAR - Putri, Givani Nurhayati; Mulyasari, Effy; Mufliva, Rosiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the issue of low mathematical conceptual understanding among Phase B students, particularly in the topic of bar charts. This condition arises because learning activities have not fully provided opportunities for students to connect mathematical material with their real-life experiences. In addition, the instructional materials used have not been optimal in presenting concrete and easily understandable contexts. To address this issue, learning materials are needed that go beyond theoretical content and present contextual situations closely related to students' daily lives. Learning materials based on Realistic Mathematics Education (RME) were developed to help students construct mathematical understanding through relevant, realistic, and meaningful learning experiences. This study aims to analyze and describe the effectiveness of RME-based learning materials in improving students’ conceptual understanding in the topic of bar charts. A quantitative method was employed using a pre-experimental design in the form of a One-Group Pretest-Posttest Design. Data were collected through tests administered before and after the intervention. The results show that the use of RME-based learning materials is reasonably effective in enhancing students' mathematical conceptual understanding, indicated by an n-gain score of 0.6469, which falls into the medium effectiveness category.